2015
DOI: 10.1606/1044-3894.2015.96.19
|View full text |Cite
|
Sign up to set email alerts
|

Reflections on Theory and Outcome Measures for Fatherhood Programs

Abstract: Responsible fatherhood programs have proliferated in the United States during the past several decades, yet few studies have been conducted of their effects on fathers and children. Evaluation of these programs requires attention to 2 questions that have not been adequately addressed: What are the specific outcomes expected from fathers' participation in programs, and how do we measure those outcomes? In this article, we suggest 3 theoretical frameworks for fatherhood programs: attachment theory, family system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 22 publications
0
22
0
1
Order By: Relevance
“…Second, the measure of fathers' positive engagement used in this study assessed the frequency of fathers' involvement in developmentally appropriate activities with children at one point in time. The validity of frequency measures for nonresident fathers is unclear (Fagan & Kaufman, ), which influenced our decision to focus on resident fathers in the present study, which in turn narrows the generalizability of our findings. Also, the observed quality of father–child interaction was not measured in the FFCWS.…”
Section: Discussionmentioning
confidence: 95%
“…Second, the measure of fathers' positive engagement used in this study assessed the frequency of fathers' involvement in developmentally appropriate activities with children at one point in time. The validity of frequency measures for nonresident fathers is unclear (Fagan & Kaufman, ), which influenced our decision to focus on resident fathers in the present study, which in turn narrows the generalizability of our findings. Also, the observed quality of father–child interaction was not measured in the FFCWS.…”
Section: Discussionmentioning
confidence: 95%
“…We also point to the importance of conceptual work in developing theoretical frameworks to inform programme design and shed light on evaluation data (Fagan & Kaufman 2015). Our review has revealed that few father-related measures are used in the evaluation of divorce-related parenting programmes, and where they are present, they are not necessarily reported on.…”
Section: Resultsmentioning
confidence: 99%
“…Evaluators, researchers, and practitioners alike will need to ask ‘What counts for positive change in relation to fathering? How do we measure and understand the effects of positive father involvement for children, families, and communities?’ Efforts to improve the quality of father‐related indictors both for research and programme evaluation have been initiated in the USA through the Fatherhood Research and Practice Network (Fagan & Kaufman ).…”
Section: Need For Father‐related Indicatorsmentioning
confidence: 99%
“…A newer body of research examining father engagement among a low-income, nonresident population suggests that these fathers also play an important role in their children's development. Furthermore, nonresident, low-income fathers face unique challenges (Arditti, 1992;Edin & Nelson, 2013) that may predispose them to experiencing a multitude of risk factors associated with less competency in parenting (Cabrera, Fagan, Wight, & Schadler, 2011;Harper & Fine, 2006); they may also experience difficulties enacting a parenting role (Fagan & Kaufman, 2015;King & Sobolewski, 2006). However, although research has shown positive effects of engagement on resident and nonresident children, it is reasonable to expect that resident and nonresident fathers will engage in different fathering activities (or that the underlying structure of involvement differs) because nonresident fathers often do not have daily contact with their children (Cabrera et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the U.S. Department of Health and Human Services currently encourages programs to partner with researchers as well as to use measures that are culturally sensitive (Fagan & Kaufman, 2015). We believe this measure to be the first that has been validated for nonresident fathers with children in different age groups.…”
mentioning
confidence: 99%